PENGARUH APLIKASI GEL EKSTRAK MEMBRAN KULIT TELUR BEBEK 10% TERHADAP KEPADATAN SERABUT KOLAGEN PADA PROSES PENYEMBUHAN LUKA GINGIVA - Agung Ikaputri Mulatpeni Novitasari; Recita Indraswary; Rosa Pratiwi (ODONTO : Dental Journal, 2017)
Background: Several processes in a teeth treatment often inflict wound ingingiva. Collagen is the key component of the wound healing. The collagen roles in advancing wound healing particularly, triggering the synthesis to induces collagen and cellular migration, and also inducing clotting cascades. Wound treatment using natural product is potential in accelerating wound healing, in particular duck egg membrane which contains collagen, glucosamine, and hyaluronic acid. This study aims to find out the influence of gel extract application of duck egg shell membrane 10 % towards collagen solidity on gingiva wound recovery process (study of Rattus norvegicus).Method: The subjects of the study consist of 20 male Rattus norvegicus aged 2-3 months which were given wound on labial gingiva of the maxillary central incisors with punch biopsy. The samples were divided into 2 groups, they were positive control group (Aloclair Gel®) and experimental group (gel extract of duck egg shell membrane 10%), each of them was treated topically twice a day for one minute.The assessment of collagen fiber was done by giving score over the collagen fiber solidity of the histological tissue through 6 points of view. The observer done by two person (blind interpretation) score of collagen fiber solidity.Result: The analysis result showed that there was a significant difference on collagen fiber solidity (p>0,05) between positive control groups and experimental group on the 3rd, 7th, and 14th day.Conclusion: This study concludes that the application of topical gel extract of duck egg shell membrane 10% affects the improvement of collagen fiber solidity on the process of healing gingiva wound on Rattus norvegicus